Irony and musical intermediality in Vals by Francesc Trabal (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
This paper analyzes the musicalization of the fiction present in Vals, the most valued novel of Francesc Trabal. The present article suggests a different reading of this novel based on the concept of intermediality and through two axes: imitation and thematization (paratextual, contextual and intratextual one). In this sense, a very close relation between this musicalized fiction and the notion of metafictional irony is observed and it helps to understand the ludic proposal established by Trabal.
Keywords: Irony; intermediality; musicalization of fiction; Francesc Trabal